The effects of the EU Cohesion Policy on regional economic growth: Using structural equation modelling for impact assessment - Ambre Maucorps; Stefan Jestl; Roman Römisch (The Vienna Institute for International Economic Studies (wiiw), 2020)
This paper analyses the effects of the EU Cohesion Policy (CP) on the economic growth of 276 European NUTS-2 regions between 2008 and 2016. Using a structural equation model (SEM) consisting of both a measurement component (with two latent variables) and a structural component, we estimate the impact of CP funding on the growth of GDP per capita across EU regions. The estimation also enables us to predict changes in the growth of GDP per capita based on a scenario of CP funding reallocation between member states. Overcoming the limitations of traditional linear regression, SEM modelling proves to be a promising method for impact evaluation, also allowing for the inclusion of indirect causal paths and feedback loops to depict, for example, cross-border economic spillover effects.
Keywords: C38; C39; R11; R12; R58; 330; Cohesion Policy; regional economic growth; structural equation modelling